ASYMMETRIC HYSTERESIS LOOPS IN CO-BASED FERROMAGNETIC-ALLOYS - SHIN, KH; GRAHAM, CD; ZHOU, PY (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1992)
Amorphous ferromagnetic alloys annealed below the Curie point in a small magnetic field develop a reproducible, asymmetric hysteresis loop. If the direction of the field during annealing is regarded as +, the magnetization reversal from + to - occurs in a single irreversible Barkhausen jump, but the reversal from - to + is smooth and reversible with its slope determined by the demagnetizing field of the sample. Various other features of this phenomenon are described. The measurements reported here were carried out on ribbons of Co70.5Fe4.5Si10B15.
Keywords: ANISOTROPY